The Unique Role Of Biomarkers In The Diagnosis Of Joint Destruction In Patients With Reactive Arthritis (Texas Journal of Medical Science, 2024)
In the world, the problem of diagnosing reactive arthritis has not yet been solved, and a number of studies are being carried out to study the practical significance of an accurate diagnosis of this disease in the early stages. We defined mechanism of cartilage early destruction in the development of apparent structural alterations in joints in reactive arthritis and its role in the deterioration of articulate syndrome.